2016
DOI: 10.1186/s12909-016-0706-1
|View full text |Cite
|
Sign up to set email alerts
|

The coping strategies during medical education predict style of success in medical career: a 10-year longitudinal study

Abstract: Background: The stress associated with the physician's work is generally acknowledged and is related to well-being and life satisfaction. The presented study was designed to extract the role of coping strategies in identifying differentiated styles of success in a medical career during medical education. Methods: The participants were examined when they applied to medical school and each subsequent academic year. The final study took place four years after graduation. The baseline questionnaire measured coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 28 publications
0
24
0
4
Order By: Relevance
“…In the context of higher education, adaptive coping has been associated with emotional intelligence (Thomas, Cassady, & Heller, 2017), motivation (Struthers, Perry, & Menec, 2000), optimism (Perera & McIlveen, 2014), satisfaction with the chosen career (Tartas et al, 2016) and positive commitment to studies (Bonneville-Roussy, Evans, Verner-Filion, Vallerand, & Bouffard, 2017), while maladaptive coping has been associated with low levels of life satisfaction (Saklofske, Austin, Mastoras, Beaton, & Osborne, 2012), negative affect and stress among university students (Bonneville-Roussy et al, 2017). In addition, previous research suggested that adaptive coping strategies are associated with academic performance (Saadu & Adesokan, 2013;Schellenberg & Bailis, 2016), whereas avoidant maladaptive coping strategies are associated with poorer academic achievement (MacCann, Fogarty, Zeidner, & Roberts, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of higher education, adaptive coping has been associated with emotional intelligence (Thomas, Cassady, & Heller, 2017), motivation (Struthers, Perry, & Menec, 2000), optimism (Perera & McIlveen, 2014), satisfaction with the chosen career (Tartas et al, 2016) and positive commitment to studies (Bonneville-Roussy, Evans, Verner-Filion, Vallerand, & Bouffard, 2017), while maladaptive coping has been associated with low levels of life satisfaction (Saklofske, Austin, Mastoras, Beaton, & Osborne, 2012), negative affect and stress among university students (Bonneville-Roussy et al, 2017). In addition, previous research suggested that adaptive coping strategies are associated with academic performance (Saadu & Adesokan, 2013;Schellenberg & Bailis, 2016), whereas avoidant maladaptive coping strategies are associated with poorer academic achievement (MacCann, Fogarty, Zeidner, & Roberts, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The common strategies used were positive reframing, planning, acceptance, and active coping. A recent study examined the relationship between the coping strategies used during medical school and the style of success in their medical career (24). The authors concluded that students who take action and deal directly with a problem have a low incidence of burnout, earn the highest income and have the highest quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Three styles of success in a medical career were identified based on significant differences between them in terms of: -postgraduate medical competence, -satisfaction with medicine as a career, -work stress and burnout, -quality of life [25][26][27].…”
Section: Dependent Variablesmentioning
confidence: 99%
“…The "Clever -satisfied with life" is the least committed to their work, but they derive the most benefit from it. The "Bright -competent" could be characterized as the most competent, nevertheless, they have problems with managing their lives [25][26][27]. The presented study was designed to describe the role of the system values during medical education in determining styles of occupational success in a medical career within 4 years after graduation, basing on our model of success.…”
Section: Introductionmentioning
confidence: 99%